Explanation :
Let $ 3-\mathrm\phi $ fault occurs at $ \mathrm t=0 $
$ \Rightarrow\;\;{\mathrm P}_\mathrm e=0\;\mathrm{for}\;\mathrm t\geq0^+ $
Now, swing equation for $ \mathrm t\geq0^+ $
$ \begin{array}{l}\;\;\;\;\frac{2\mathrm H}{{\mathrm\omega}_\mathrm s}\frac{\mathrm d^2\mathrm\delta}{\mathrm{dt}^2}={\mathrm P}_\mathrm m\\\;\;\;\;\;\;\;\frac{\displaystyle\mathrm d^2\mathrm\delta}{\displaystyle\mathrm{dt}^2}=\frac{{\mathrm P}_\mathrm m{\mathrm\omega}_\mathrm s}{2\mathrm H}\\\;\;\;\;\;\;\;\;\;\frac{\mathrm{dδ}}{\mathrm{dt}}=\frac{{\mathrm P}_\mathrm m{\mathrm\omega}_\mathrm s}{2\mathrm H}\mathrm t+\mathrm C\\\;\;\;\;\;\;\;\;\;\;\mathrm C=\frac{\mathrm{dδ}}{\mathrm{dt}}\vert_{\mathrm t=0^+}=\mathrm\omega(\mathrm t=0^+)-{\mathrm\omega}_\mathrm s\\\;\;\;\;\;\;\;\;\;\;\mathrm C={\mathrm\omega}_\mathrm s={\mathrm\omega}_\mathrm s=0\;(\mathrm\omega(\mathrm t=0^+)={\mathrm\omega}_\mathrm s)\\\;\;\;\;\;\;\;\;\;\frac{\mathrm{dδ}}{\mathrm{dt}}=\frac{{\mathrm P}_\mathrm m{\mathrm\omega}_\mathrm s}{2\mathrm H}\mathrm t\\\Rightarrow\;\;\;\;\;\;\mathrm\delta=\frac{{\mathrm P}_\mathrm m{\mathrm\omega}_\mathrm s}{4\mathrm H}\mathrm t^2+\mathrm C'\\\;\;\;\;\;\;\;\;\;\mathrm C'=\mathrm\delta\vert_{\mathrm t=0^+}={\mathrm\delta}_0\\\;\;\;\;\;\;\;\;\;\;\;\mathrm\delta=\frac{{\mathrm P}_\mathrm m{\mathrm\omega}_\mathrm s}{4\mathrm H}\mathrm t^2+{\mathrm\delta}_0\;\;\;\;\end{array} $
Now in problem,
$ \begin{array}{l}\mathrm\delta(\mathrm t=0.02)\\=\frac{1\times2\times180\times50\times0.02^2+5^\circ}{4\times2}=5.9^\circ\\\end{array} $